Integrated transcriptome landscape of ALS identifies genome instability linked to TDP-43 pathology - Oliver J. Ziff; Jacob Neeves; Jamie Mitchell; Giulia Tyzack; Carlos Martinez-Ruiz; Raphaelle Luisier; Anob M. Chakrabarti; Nicholas McGranahan; Kevin Litchfield; Simon J. Boulton; Ammar Al-Chalabi; Gavin Kelly; et al. (Nature Communications, 2023)
Abstract Amyotrophic Lateral Sclerosis (ALS) causes motor neuron degeneration, with 97% of cases exhibiting TDP-43 proteinopathy. Elucidating pathomechanisms has been hampered by disease heterogeneity and difficulties accessing motor neurons. Human induced pluripotent stem cell-derived motor neurons (iPSMNs) offer a solution; however, studies have typically been limited to underpowered cohorts. Here, we present a comprehensive compendium of 429 iPSMNs from 15 datasets, and 271 post-mortem spinal cord samples. Using reproducible bioinformatic workflows, we identify robust upregulation of p53 signalling in ALS in both iPSMNs and post-mortem spinal cord. p53 activation is greatest with C9orf72 repeat expansions but is weakest with SOD1 and FUS mutations. TDP-43 depletion potentiates p53 activation in both post-mortem neuronal nuclei and cell culture, thereby functionally linking p53 activation with TDP-43 depletion. ALS iPSMNs and post-mortem tissue display enrichment of splicing alterations, somatic mutations, and gene fusions, possibly contributing to the DNA damage response.